The Gilbertine priories of Alvingham and Bullington : their endowments and benefactors - Golding, BJ (1979)
This thesis has two themes. In the first place it is a study of the development of the estates of two small Gilbertine houses in north Lincolnshire from their foundation c.1150 to c.1300, by which date their holdings had reached their largest extent. It is clear that the great majority of the houses' properties had been obtained by c.1200 and by this date granges had been established at the largest holdings. At the same time the priories were receiving grants of churches, the income from which provided over half of their income by the end of the thirteenth century. Secondly, I have examined the benefactors of these communities, most of whom were drawn from the ranks of the lesser lords of the region or from the free peasants. I have attempted to demonstrate how the fortunes of the priories and their economic growth were dependent upon the economic condition of their benefactors. Many of these men had little land to grant to religious houses and often their families were declining in importance. As a result their grants in favour of the priories were increasingly small. Evidence for both the endowments of the priories and for the condition of their benefactors is largely confined to charters, of which a large number survive for both priories. Though it has not proved possible to describe the economy of either priory in any details the evidence does allow a detailed study of the creation of the estates of these small houses and an assessment of their importance in the life of their region.